Effect of Methylation on Storage Properties of Lacticaseibacillus paracasei as Analyzed by Untargeted Metabolomics - YOU Mingkun, ZHANG Wenyi (Shipin Kexue)
Lacticaseibacillus paracasei Zhang is an excellent strain with probiotic properties such as immunomodulatory and antioxidant activities. DNA methylation is an important epigenetic mechanism that plays a key role in many physiological processes in bacteria. In order to better utilize the strain, this study focused on the effect of methylation on the storage properties of two starter cultures of L. paracasei Zhang and its DNA methylation mutant (ΔpglX) at 30 ℃. The results showed that after 90 d of storage, the viable number of the mutant significantly increased compared with the wild type (P < 0.01). Using untargeted metabolomics, 269 differential metabolites were observed in the mutant compared with the wild type, which were mainly enriched in the nucleotide metabolism, purine metabolism, pyrimidine metabolism, citrate cycle, glyoxylate, and dicarboxylate metabolism pathways in the negative ion mode. In the positive ion mode, they were mainly enriched in the biotin metabolism pathway. These findings confirmed that DNA methylation could improve the storage properties of L. paracasei Zhang through the generation and utilization of carbohydrates and fatty acids.